Personal Correlates of Support for Medical and Recreational Cannabis Legalization in Australia - Chiu, Vivian; Chan, Gary; Hall, Wayne; Hides, Leanne; Lim, Carmen; Leung, Janni (Frontiers in Psychiatry, 2021)
Introduction and Aims: Increasingly more Australians are in favor of legalizing medical and recreational cannabis use. This paper explored the personal characteristics of those who supported each of these policies in Australia. Design: Cross-sectional national survey. Methods: This study included 21,729 participants aged 18 years and above who responded to the 2016 National Drug Strategy Household Survey. Participants were provided the assurance of confidentiality for their participations. Logistic regression models were used to examine the relationships between personal characteristics and support for the legalization of medical and recreational cannabis. Results: Overall, 77 and 40% of participants supported the legalization of medical and recreational cannabis respectively. People of older age were more likely to support medical cannabis legalization while those who supported legalization of recreational cannabis use were more likely to be younger. Medical cannabis supporters were more likely to report chronic pain (OR = 1.44, 95% CI: 1.04, 2.00) while recreational cannabis supporters were more likely to suffer high level of psychological distress (OR = 1.28, 95% CI: 1.14, 1.43). Experience with cannabis use was strongly associated with supportive attitudes, with recent cannabis users almost 14 times (OR = 14.13, 95% CI: 5.37, 37.20) and 34 times (OR = 33.74, 95% CI: 24.22, 47.01) more likely to support the legalization of medical and recreational cannabis use, respectively. Discussion and Conclusions: The majority of Australians approve the legalization of cannabis for medicinal purposes but most remain cautious about legalizing recreational cannabis use. The sociodemographic and clinical profile of supporters of medical and recreational legalization suggests a potential interaction of self-interests and beliefs about the harms of cannabis use.